The Cycle of St. Demetrius in the Patriarchate of Peć - III - - Pajić, Sanja R. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The painted biography of the patron saint of the church of St. Demetrius in the complex of the Patriarchate of Peć is preserved in the middle zone of the nave. Following the northern wall, with episodes inspired by the texts of the Passion of Saint Demetrius, the cycle continues on the south wall, where two of the former four representations remain, namely: The Dormition of Demetrius and Saint Demetrius Saves Thessaloniki from the Enemy. Both scenes have been partially damaged, with the lower parts painted over during the restoration in the second decade of the 17th century. The Dormition of Saint Demetrius The Dormition of Saint Demetrius is painted in the southeast corner of the nave. The beginning of the legend is legible. Two more compositions with the same iconography have been preserved. One is a miniature in the Menologion in Oxford (MS. Gr. th. f. 1, fol. 55) (c. 1330–35), and the other is a severely damaged fresco in King Marko’s Monastery (1376/77, the Republic of North Macedonia). The iconographic scheme of the service over the body of the deceased is well known in medieval art. Since the Passio texts describe Demetrius’ martyrdom, scholars have questioned the source and meaning of the scene. At first they thought that it illustrated Bishop Eusebius praying before the relics of St. Demetriusto save Thessaloniki from the enemy, according to the description from the 14th homily of the First Book of Miracula. Later, the assumption was made, accepted to this day, that it was the death/entombment of the saint. The textual prototype was found in the sticheron of the patriarch Germanus on the celebration day of Saint Demetrius, from where this theme entered the iconography. Recently, the scene was interpreted as a liturgical ceremony over the saint’s tomb in the Thessaloniki church.Knowing the circumstances in which it was created could contribute to a better understanding of the topic. The representation of the dead Demetrius is associated with the reform of the cult after the appearance of the myron, at the beginning of the 11th century at the latest. This is evidenced by reliquaries and enkolpia for myron and/or blood of the saint (11th/12th–14th centuries), which copy the appearance of a myron-gushing tomb. They are characterized by a double lid with superimposed figures of Saint Demetrius. On the outer cover Demetrius is in the orante pose –which has been interpreted as a sarcophagus, while the inside shows a dead saint – that is, a representation ofthe saint’s myron-exuding body relic. The myron-gushing tomb received its equivalent in painting, as well, sublimated through the representation of the tomb with the reclining figure of Demetrius in the orante pose. Two paintings are known, both of which are sometimes erroneously cited among scholarsand preserved in Serbian art as the Entombment of Saint Demetrius (in the southern chapel of the Church of Our Lady of Ljeviš, 1309–13, in Kosovo and Metohija, and, as part of the scene The vision of angels of an illustrious and Demetrius’ refusal to abandon Thessaloniki, 1335–48 in Dečani, Kosovo and Metohija).Along with this theme, the iconography of the service over Demetrius’ relics was also formed. At this time, a legend appeared that, by order of Emperor Maximian, Demetrius’ body was thrown into a well under the Thessaloniki basilica, connected to the crypt or “lower church”. Perhaps the changed cult brought more novelties, which could have influenced the appearance of new iconography, yet this question still remains open to debate.The service over the saint’s body is officiated by archbishops surrounded by singers, led by a choirmaster and a young kanonarchos, all distinguished by headpieces known as skaranikon. The rest of the entourage were identified as believers or Christians who buried the saint, that is, young noblemen, but in fact they were members of minor order.The building in the background is most often identified as the famous ciborium from the Thessaloniki basilica, which was a cult centre during the early Christian period. Although the fresco in Peć is unique compared to the other preserved representations, in which the tomb is shown with an open ciborium-baldachin, they are also considered to convey a realistic image of a contemporary tomb. This testifies to the impossibility of reaching a reliable conclusion about the closeness of the painted and real construction, where at the time of the creation of the fresco, the centre of the cult was no longer a ciborium, but a myron-gushing tomb. Saint Demetrius Saves Thessaloniki from the Enemy The last preserved fresco, from whose inscription the name of Demetrius can be read, illustrates the miracle of the defense of Thessaloniki against the enemy. The event is described in the 14th homily of the First Book of Miracula. The majority of researchers have accepted the opinion that homilies 13–15 describe the attack of the army of Avars and Slavs on Thessaloniki that took place in 586, although a similar event in 597 cannot be ruled out.The iconographic scheme of the fresco in Peć comes right after the text. In the cycles of the Middle Ages, only two more compositions with Demetrius saving Thessaloniki from the enemy have been preserved. In terms of concept, and despite the differences in the processing of details, the fresco in Peć is close to the depiction in Dečani (1335–48). In previous research, the inscription on the fresco in Dečani attracted more attention than the iconography, with the explanation that it was about saving Thessaloniki from the Kumans. This gave scholars a reason for different interpretations of the meaning of the illustration, although it is most likely that it is the very event mentioned in the inscription, for the artistic articulation of which the iconography created according to a much older source was used.The composition on the reliquary in Vatoped, with the enemy’s cavalry under the city walls behind which the saint is using the spear to defeat the barbarian, will not be repeated. Searching for the source is made difficult by the fact that no text was written, hence the opinions of scholars about the meaning of the scene are dissonant, although most believe that it is about the defense of Thessaloniki against the siege of the Avars and the Slavs.The walls within which the sacred building is located represent a long-established ideogram for the city, identified as the place of events – Thessaloniki with the Basilica of Saint Demetrius.The hagiography of Saint Demetrius was painted in the nave of the church of the same name in the Patriarchate of Peć, following the practice that prevailed in the 14th century. So far, it has not been a specific research topic, nor has it been discussed in the context of known cycles. About 13 artistic biographies of saints created at the end of the 13th and in the 14th century in the Byzantine, Serbian and Bulgarian art, along with individual representations of certain themes, have been published by scholars, to varying degrees. Despite the fact that the cycles are mostly incompletely preserved, as well as that part of the frescoes in Peć was partially or completely restored in the second decade of the 17th century, which raises the question of the original iconography, certain conclusions can be drawn about its concept and the iconography of individual scenes.Six out of the former eight scenes remain, according to which the Peć cycle belongs to the longer redaction. Being a complex ensemble, it consists of compositions based on the life of the saint, concentrated on the north wall of the nave of the church, and scenes of miracles on the opposite wall, of which only one remains, along with a composition of a special theme with the representation of the Dormition of St. Demetrius. Hagiographic scenes illustrate the most significant events from the texts of the Passion representing an indispensable part of the cycle. Scenes of miracles were painted less often, so the miraculous saving of Thessaloniki from the enemy is preserved in three cycles only. The theme of help in a specific situation has most likely surpassed its source over time, becoming an allusion to the enemies of Christians, and the proof of the miraculous protection of Demetrius as the holy warrior, not only when it comes to Thessaloniki, but war in general. Hence it is not surprising that it was included in the cycle, for now it can be said with confidence, in the 14th century. Since the legend has not been preserved, the question remains whether there was a deeper motive for illustrating this event in the church in Peć. The scene with the representation of the Dormition of St. Demetrius, and the rarely shown one, known from three medieval cycles, remain of unclear origin, but its source should probably be sought in cult practice of the 14th century. This episode, together with the Passion of St. Demetrius, is prominently placed next to the altar partition, which is why the cycle began in the northwest corner of the nave.The general language of Byzantine iconography was used to shape the compositions. Certain frescoes from Peć show similarities with preserved illustrations of the same outline, but they are mostly unique. Iconographically, St. Demetrius blessing St. Nestor and St. Nestor killing Lyus stand out, bearing the caveat in mind that this is a composition that undoubtedly underwent some changes during the copying process. As a whole, the illustrations from Peć represent a unique accomplishment, the closest analogies of which can be found on the monuments of the 14th century created in the Serbian art. Probably at this time there were certain changes in the cycle, primarily following the cult and way of honouring saints, with a greater tendency towards narration as a general trend in the art of this time.Finally, it is necessary to refer to two more cycles. The first one, in poor condition, was created in the church of Saint Demetrius in the village of Leivadi in Crete (1315/16), whose painting is strongly influenced by Western art. The iconography of the scene of the Passion of Saint Demetrius, with the saint with his back turned and falling to his knees receiving a spear blow from a soldier in Western armor, bears no resemblance to the Byzantine tradition.The second cycle was recently discovered in the chapel of the Dodorka monastery in Georgia’s Davitgareji Desert (late 12th–early 13th century). Some of the compositions possess the iconography not found anywhere (St. Demetrius drops an honorary regalia before Emperor Maximian and the Martyrdom of St. Demetrius, with the dismembered body of the saint, while his chlamys is in the foreground), i.e., it shows details that do not appear or are rare in Byzantine painting (Saint Demetrius blessing Saint Nestor - both of them standing, and Nestor is unarmed, and Saint Nestor kills Lyus - with a young Christian fighter plunging a spear into the body of a fallen gladiator, in the arena without manganese and without the figure of the emperor in the lodge). The Dodorka cycle has no parallels in Georgian and Byzantine art. Significant iconographic peculiarities, and the fact that the appearance of the frescoes was dictated by a local source (Georgian version of the Passion from the 11th century) and specific needs (the emphasis on the chlamys as a relic of Demetrius), complicate the questions of the model for its iconography and the connection with Byzantine art, but even more so – issuesof time and place of origin of the cycle of St. Demetrius.
Keywords: St. Demetrius; Patriarchate of Peć; Vita cycle; iconography; The Dormition of Saint Demetrius; Saint Demetrius Saves Thessaloniki from the Enemy; Georgije Mitrofanović